2011
DOI: 10.1097/mca.0b013e328342c77b
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width as a novel prognostic marker in patients undergoing primary angioplasty for acute myocardial infarction

Abstract: A high admission RDW level in patients with STEMI undergoing primary PCI was associated with increased risk for in-hospital and long-term cardiovascular mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
3
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(161 citation statements)
references
References 0 publications
4
147
3
7
Order By: Relevance
“…In a study by Uyarel et al [7], high RDW level on admission was demonstrated to be an indicator for in-hospital and long-term cardiovascular mortality in STEMI patients who underwent primary PCI. The authors revealed that increased age, Killip class > 1, DM, and high RDW were found to be predictors of cardiovascular mortality [7]. Unlike our study, these authors used a retrospective database.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study by Uyarel et al [7], high RDW level on admission was demonstrated to be an indicator for in-hospital and long-term cardiovascular mortality in STEMI patients who underwent primary PCI. The authors revealed that increased age, Killip class > 1, DM, and high RDW were found to be predictors of cardiovascular mortality [7]. Unlike our study, these authors used a retrospective database.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated RDW typically indicates increased destruction of red cells or nutritional de- ficiency such as vitamin B12, iron, and folate, or is observed after blood transfusion. In addition, many recently published studies reported that increased RDW levels are correlated with poor prognosis in many acute-chronic cardiac and non-cardiac events [7,9,14], even in the case of adjustments for multiple potential confounders, including anemia. In a study by Uyarel et al [7], high RDW level on admission was demonstrated to be an indicator for in-hospital and long-term cardiovascular mortality in STEMI patients who underwent primary PCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence shows that RDW is closely associated with atherosclerotic coronary artery disease, fatal and non-fatal cardiovascular disease. Importance of RDW in cardiovascular diseases increases further with easy access and no additional cost of RDW (12)(13)(14). The relationship between RDW and IMT was shown in several studies.…”
Section: Resultsmentioning
confidence: 99%